ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH UNTUK MENYIMPAN DANA PADA BANK SYARI’AH DI KOTA PURWOKERTO (Studi pada BRI Syariah dan Bank Muammalat Cabang Purwokerto) - Nita Despri Kartikasari; Hermin Endratno (Media Ekonomi, 2016)
This study was conducted to analyze the factors that influence a client's decision to deposit funds in Islamic banks. In this study, the data used is primary data by questionnaire to customers of BRI Syariah and bank Muammalat Purwokerto with a sample of 156 reaponden. In the sampling method, the author uses purposive sampling method. The analysis used in this study using validity and reliability test, classic assumption test, multiple regression analysis, and hypothesis testing F-test, t-test and the coefficient of determination (R2). The results showed that the characteristic variable bank, syariah factors, social class, reference groups, the role of family factors, factors perceived marketing stimuli simultaneously have a positive impact on the customer's decision to save in Islamic banks. Partial test results can be concluded that social class variables and variable marketing stimuli have a positive effect but not significant, while the variable characteristics of the bank, syariah factors, reference groups and family roles positive and significant impact on customer decisions. Concluded that all six variables are able to explain the customer's decision amounted to 44.5% (adjusted R-square value), while the remaining 55.5% is explained by other factors beyond the research Keyword: Factor analysis, the customer's decision, Islamic banks